A 12-Year Content Analysis of the Journal of Black Psychology (2000-2011): Implications for the Field of Black Psychology. (June 2014) - Cokley, Kevin; Awosogba, Olufunke; Taylor, Desire
A content analysis was conducted of research published in the Journal of Black Psychology ( JBP ) during a 12-year period (2000-2011). A total of 276 articles were classified into 17 content categories. Similar to the previous JBP content analysis, the most frequently published authors and institutions were identified and ranked. The most highly cited articles were also identified. In addition, gender-focused articles and articles involving racial/ethnic group comparisons were identified. The most popular areas of research and publication in the JBP were in mental health and well-being, personality and identity (i.e., racial identity), culture, and physiological functioning and health psychology. These four categories accounted for 57% of the articles published. Results of this content analysis indicate a sharp increase in research on mental health and culture, while other areas remained consistent with the previous JBP content analysis. The dearth of African-centered psychological research was also noted. Implications for the field of Black psychology in the areas of African-centered research, defining Black psychology, and conducting race comparative research are discussed.